Observational Evidence of the Association Between Handgrip Strength, Hand Dexterity, and Cognitive Performance in Community-Dwelling Older Adults: A Systematic Review - Kimi Estela Kobayashi-Cuya; Ryota Sakurai; Hiroyuki Suzuki; Susumu Ogawa; Toru Takebayashi; Yoshinori Fujiwara (Journal of Epidemiology, 2018)
Background: Deterioration of hand motor function is a possible risk factor of cognitive impairment in older adults. Despite a growing body of research, a lack of clarity exists regarding the relationships. This review offers a synthesis of existing observational studies evaluating the associations of handgrip strength and hand dexterity with cognitive performance in community-dwelling older adults. Methods: PubMed, PsycINFO, and ScienceDirect were systematically searched (search dates: 1990–2016), and relevant articles were cross-checked for related and relevant publications. Results: Twenty-two observational studies assessed the association of handgrip strength or hand dexterity with cognitive performance; none evaluated handgrip strength and hand dexterity together. Handgrip strength was associated with global cognition, mostly assessed using the Mini-Mental State Examination, cross-sectionally and longitudinally. Also, one cross-sectional and three longitudinal studies found an association with cognitive domains, such as language, memory, visuospatial ability, working memory, and processing speed. Hand dexterity was only assessed cross-sectionally in four studies. These studies found an association with cognitive domains, such as executive function. Conclusions: Although handgrip strength was associated with cognitive performance, it is unclear which variable at baseline affects the other in the long-term. Cross-sectional studies indicate an association between hand dexterity and cognitive performance, yet longitudinal studies are needed to elucidate this association. The interaction effects of both decreased grip strength and hand dexterity on cognitive performance is still unclear; therefore, future studies will need to consider the interaction of the three variables cross-sectionally and longitudinally.